2014
DOI: 10.1038/ncomms4462
|View full text |Cite
|
Sign up to set email alerts
|

Ligand substitutions between ruthenium–cymene compounds can control protein versus DNA targeting and anticancer activity

Abstract: Ruthenium compounds have become promising alternatives to platinum drugs by displaying specific activities against different cancers and favourable toxicity and clearance properties. Nonetheless, their molecular targeting and mechanism of action are poorly understood. Here we study two prototypical ruthenium-arene agents—the cytotoxic antiprimary tumour compound [(η6-p-cymene)Ru(ethylene-diamine)Cl]PF6 and the relatively non-cytotoxic antimetastasis compound [(η6-p-cymene)Ru(1,3,5-triaza-7-phosphaadamantane)Cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
240
0
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 278 publications
(260 citation statements)
references
References 59 publications
13
240
0
4
Order By: Relevance
“…29 While oxaliplatin was shown to preferentially interact with the oligonucleotide in this model system, 29 the organometallic ruthenium(arenes) turned out to be tuneable with respect to this property, depending on the inert ligands. 30 In the same setup, the drug candidate [chlorido(Z 6 -p-cymene)(N-(4-fluorophenyl)-2-pyridinecarbothioamide)ruthenium-(II)]chloride (plecstatin-1, Scheme 1A) was shown to exclusively coordinate to histidines 79 and 106 of histone 2B. 24 Then, an MS-based shotgun proteomics method was developed to identify potential protein targets of plecstatin-1 by a combination of affinity purification of cell lysates and in vitro treatment of cell cultures.…”
Section: Resultsmentioning
confidence: 99%
“…29 While oxaliplatin was shown to preferentially interact with the oligonucleotide in this model system, 29 the organometallic ruthenium(arenes) turned out to be tuneable with respect to this property, depending on the inert ligands. 30 In the same setup, the drug candidate [chlorido(Z 6 -p-cymene)(N-(4-fluorophenyl)-2-pyridinecarbothioamide)ruthenium-(II)]chloride (plecstatin-1, Scheme 1A) was shown to exclusively coordinate to histidines 79 and 106 of histone 2B. 24 Then, an MS-based shotgun proteomics method was developed to identify potential protein targets of plecstatin-1 by a combination of affinity purification of cell lysates and in vitro treatment of cell cultures.…”
Section: Resultsmentioning
confidence: 99%
“…1A, right panel) is higher than that of paddlewheel diruthenium species (Barral et al 2007(Barral et al , 2008, we decided to test the reactivity of the compound [Ru 2 Cl 2 (µ-DPhF) 3 (DMSO)] (designated OPW-Ru) (DPhF = N,N ′ -diphenylformamidinate) toward RNA. Numerous ruthenium compounds have been designed to interact with nucleic acid such as mononuclear ruthenium complexes with labile ligands (Busto et al 2013;Wu et al 2013;Adhireksan et al 2014) or tris(chelate)ruthenium(II) compounds (Song et al 2012;Li et al 2015). The existence of labile ligands in the first type of compounds allows establishing direct ruthenium-nucleic acid bonds; the coordination mode implies bond angles of 90°.…”
Section: Introductionmentioning
confidence: 99%
“…However, studies [242][243][244] with a series of ruthenium anticancer compounds revealed that DNA is not always the primary target and that these species were actually binding more strongly to proteins than to DNA. These findings clearly indicated the occurrence of significantly different modes of action, depending on the type of ruthenium complexes.…”
Section: Cancermentioning
confidence: 96%